EXPECTATION MAXIMIZATION ALGORITHM MEMPREDIKSI PENJUALAN SUSU MURNI PADA PT. SEWU PRIMATAMA INDONESIA LAMPUNG TENGAH - Waspah, Aik Isnayah; Afandi, Asep; Efendi, Dwi Marisa; Sartika, Dwi (LPPM UNIVERSITAS BINA INSAN, 2022)
Pure milk is a liquid that comes from the udder of healthy and clean cows obtained by proper milking, its natural content is not reduced or added by anything and has not received any treatment. This study focuses on selling whole milk based on the effect of promotional prices as a sales strategy. The purpose of this research is to include data mining steps so that maximum data on pure milk sales can be obtained based on the effect of promotional prices and data reduction using the expectation maximization algorithm and testing using RapidMiner 8.0. The results of the implementation of Data Mining using the expectation maximization algorithm, which are based on sales data and cut price promotional price data are in 2019-2021 the maximum promotional price (MAXx) obtained is 0.22 (22,000) and the minimum value (MINx) is 0, 15 (15000). For pure milk sales in 2019 the maximum (MAXy) sales were 0.3641 (3,641 liters) in November and the minimum value (MINy) was 0.119 (1,190), in 2020 the maximum (MAXy) sales was 0.3861 (3,861 liters) in July, and the minimum value (MINy) is 0.1925 (1.925) and in 2021 the maximum (MAXy) sales is 0.3921 (3,921 liters) in September, and the minimum value (MINy) is 0.2004 (2004) liter.